Effectiveness of an educational intervention about inhalation technique in healthcare professionals in primary care: a cluster randomized trial - Vázquez-González, Noemí; Leiva-Fernández, José; Cotta-Luque, Víctor M.; Leiva-Fernández, Francisca; Rius-Díaz, Francisca; Martos-Crespo, Francisco; Martín-Montañez, Elisa; Barnestein-Fonseca, Pilar (Frontiers in Pharmacology, 2023)
Background: Incorrect inhalation technique (IT) is an important issue for chronic obstructive pulmonary disease (COPD) patients and healthcare professionals. Studies in which counseling is carried out with healthcare professionals beforehand so that they can properly educate their patients are required. The objective of the present trial is to assess the improvement in the performance of the IT in subjects with COPD and prescribed inhaled therapy after the implementation of an educational intervention conducted by their general practitioners. Methods: A cluster randomized clinical trial was conducted. A total of 286 COPD patients received scheduled inhalation therapy from 27 general practices in seven primary care centers. A teach-back educational intervention was implemented for both healthcare professionals and patients. The primary outcome of this study was the performance of the correct inhalation technique. It is considered a good technique if all steps in the inhalation data sheet are correctly performed. The secondary outcomes were assessed using forced spirometry, the basal dyspnea index, the Medical Research Council dyspnea scale, St George’s Respiratory Questionnaire (SGRQ), and EuroQoL5D-5L for health-related quality of life. A one-year follow-up was conducted using an intention-to-treat analysis. Results: After the intervention, incorrect IT was observed in 92% of professionals and patients, with rates reaching 50% and 69.2%, respectively. The effectiveness in patients was significant, with a number needed to treat of 2.14 (95% CI 1.79–2.66). Factors related to correct IT in patients included the type of intervention, length of intervention (>25 min), good pulmonary function, age (youngest <=65, oldest >83), and less limitation of activity due to dyspnea. There was no relation with the cluster. Conclusion: This study shows the effectiveness of direct inhaler technique training provided by a trained professional on an appropriate timescale (for example, a specific consultation for medication reviews), aiming to help subjects improve their performance using the teach-back method. This could be an encouraging intervention to improve medication adherence and health promotion in people with COPD. Clinical Trial Registration:clinicaltrials.gov, identifier ISRCTN93725230.